Heroes of resiliency and reciprocity: teachers' supporting role for reconceptualizing superhero play in early childhood settings. (1st October 2016) - Harris, Kathleen I.
Abstract: Superhero play is a specialised form of fantasy play with considerable appeal to young children. During superhero play, children have opportunities to pretend and often to play different types of roles within a safe and caring environment. When guided appropriately in an early childhood classroom, superhero play gives young children opportunities to gain a sense of mastery and empowerment as well as developmentally appropriate benefits by improving language skills, problem-solving and cooperation with peers. By recognising and modelling the characteristics of resiliency and promoting kindness with peers during superhero play, teachers can encourage children to be kind and resilient heroes to classroom friends. As today's classrooms increasingly include diverse members, it is important for young children to understand and appreciate the peers they play and learn with at school. The result may be a richer learning experience and may break down barriers that can produce unfairness, bullying and aggressive behaviours. This article explores the essence of superhero fantasy play along with its benefits for young children. In addition, the article examines the challenge of superhero play in classrooms for early childhood educators by exploring teachers' roles in play. A new pedagogy for supporting superhero play is introduced, addressing spiritual and educational concerns by suggesting ways in which teachers can increase resiliency, encourage new friendships and build classroom community among peers during play and classroom activities.